2010
DOI: 10.21608/jssae.2010.75819
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Compost, N-Mineral and Humic Acid on Yield and Chmical Composition of Wheat Plants

Abstract: Two field experiments were carried out at the experimental farm of El-Ismailia Agric. Research station, during two successive winter seasons of 2007/2008-2008/2009 to study the effect of different levels of nitrogen fertilizers 0,25, 50, 75 and 100kg N/fed. from recommended dose (100kg/fed) with or without composted rice straw and / or humic acid on yield, yield components, chemical composition of wheat plant and its attributes as well as NPK uptake of wheat grain and straw, and protein content. A three way ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 0 publications
14
28
0
1
Order By: Relevance
“…The increase in N, P and K uptake of wheat straw related with rising N fertilizer rates may be due to the role of N fertilizer in increasing growth of wheat through heartening plants to uptake other macro and micronutrients as well as accordingly enhancing photosynthesis. These results are in agreement with those reported by Seadh et al, (2008); Antoun et al, (2010) and Shirazi et al (2014), they concluded that the attractive effect of higher N fertilizer rate on yields and quality of grain can be easily ascribed to the nitrogen which think as one of the major nutrient for plant nutrition and it enlarges the vegetative plant growth and forms strong plants with long spikes. Furthermore, nitrogen give confidences plant to uptake other macro and micronutrients activating, thus plants growth, accordingly increasing measurements of growth and all yield attributes.…”
Section: N P and K Uptake (Kg Fed -1 ) As Well As Protein % Of Wheatsupporting
confidence: 93%
“…The increase in N, P and K uptake of wheat straw related with rising N fertilizer rates may be due to the role of N fertilizer in increasing growth of wheat through heartening plants to uptake other macro and micronutrients as well as accordingly enhancing photosynthesis. These results are in agreement with those reported by Seadh et al, (2008); Antoun et al, (2010) and Shirazi et al (2014), they concluded that the attractive effect of higher N fertilizer rate on yields and quality of grain can be easily ascribed to the nitrogen which think as one of the major nutrient for plant nutrition and it enlarges the vegetative plant growth and forms strong plants with long spikes. Furthermore, nitrogen give confidences plant to uptake other macro and micronutrients activating, thus plants growth, accordingly increasing measurements of growth and all yield attributes.…”
Section: N P and K Uptake (Kg Fed -1 ) As Well As Protein % Of Wheatsupporting
confidence: 93%
“…The significant promotive effect of (60 kg N fed -1 + 2 t compost fed -1 ) combination could lead to increase N availability in fodder beet root vicinity with the result that N absorption was increased leading to increase the rate of photosynthesis and metabolic processes, physiological activities of meristemic tissues and dry matter accumulation, consequently, fresh and dry top and root yields of fodder beet got significantly increased. This explanation is supported by (Salem, 2000 andAntoun et al, 2010). The positive effect of compost on fresh and dry top and roots of fodder beet could be associated with its lowering soil pH that could enhance some nutrient availability in the soil and its improving soil physical characteristics in favor of plant root development.…”
Section: -Effect Of Mineral Organic Compost and Bio Fertilizers On mentioning
confidence: 85%
“…Because, the essential role of major nutritional elements in plant growth is widely recognized, an effort has made in this review to focus on the synergistic effects of this (H.S) and nutritional elements in the presence of complete and considered to be optimal nutrient supply. Antoun et al (2010) found that addition of humic substances markedly increased wheat plant height, panicle length, 1000-grain weight, grain, straw yield/fed., protein content in grain and NPK uptake of both grain and straw.…”
Section: Cyanobacteriamentioning
confidence: 95%